Modifikasi Bak Pendingin Pada Proses Produksi Asap Cair Tempurung Kelapa Untuk Peningkatan Volume Produksi - Abdul Fatah, Kemas Muhammat; Kuncoro, Dwi (Infotekmesin, 2022)
Increasing the production of liquid smoke is an attempt to raise the utilization of coconut shells as a by-product of the coconut fruit. The distillation process is a way to produce liquid smoke and condensation occured in the cooling bath. Improving the cooling bath can increase the production volume. This study aims to determine the performance of the cooling bath in 10 experiments with variations in the level of the water flow rate factor of 20 liters/minute, 25 liters/minute, 30 liters/minute, and the level of the airflow velocity factor of 35 m/s, 40 m/s. and 45 m/s. Modifying the cooling bath can improve its performance and increase the volume of liquid smoke. The largest increase of 36.14% was achieved at the water flow rate in the level of 30 liters/minute and the airflow velocity factor in the level of 45 m/s, at 26.2oC of the cooling bath temperature.